Lychee-like FeS2@FeSe2 core–shell microspheres anode in sodium ion batteries for large capacity and ultralong cycle life. Issue 36 (31st August 2017) - Zhao, Wenxi; Guo, Chunxian; Li, Chang Ming
Abstract : Sodium ion batteries (SIBs) are one promising power source with low cost, abundant resource supply and good environmental benignity, but the development of a large capacity and long cycle life anode remains a great challenge. Abstract : Sodium ion batteries (SIBs) are one promising power source with low cost, abundant resource supply and good environmental benignity, but the development of a large capacity and long cycle life anode remains a great challenge. Unique lychee-like FeS2 @FeSe2 core–shell microspheres were fabricated and used as an anode material for SIBs, delivering a high discharge capacity of 350 mA h g −1 at 1 A g −1 after 2700 cycles, and even up to 301.5 mA h g −1 at 5 A g −1 after 3850 cycles with over 97% coulombic efficiency. The significant enhancement in performance is contributed by the structure and chemistry of FeS2 @FeSe2 core–shell microspheres, which are stacked into a uniformly distributed porous spheres-based electrode for fast mass transport to access both the FeS2 core and the FeSe2 shell, and the more conductive shell FeSe2 encapsulates the less conductive FeS2 for fast electron transfer/transport while preventing the aggregation of active FeS2 for a large reaction surface. This model may reveal an important scientific insight that the size of microspheres of less than diffusion thickness can make the electrochemical reaction take place without a diffusion limit like a surface-controlled pseudocapacitive behavior for an extremely rapid electron transport pathway. This study vividly demonstrates the great synergistic effects of the physics and chemistry of a nano/microstructure on the performance of energy storage devices, and the approach to the design of such a core–shell structure may have universal significance for the large capacity and long cycle life of SIBs.